The structure of a β2-microglobulin fibril suggests a molecular basis for its amyloid polymorphism. Issue 1 (December 2018) - Iadanza, Matthew; Silvers, Robert; Boardman, Joshua; Smith, Hugh; Karamanos, Theodoros; Debelouchina, Galia; Su, Yongchao; Griffin, Robert; Ranson, Neil; Radford, Sheena
Abstract All amyloid fibrils contain a cross-β fold. How this structure differs in fibrils formed from proteins associated with different diseases remains unclear. Here, we combine cryo-EM and MAS-NMR to determine the structure of an amyloid fibril formed in vitro from β2 -microglobulin (β2 m), the culprit protein of dialysis-related amyloidosis. The fibril is composed of two identical protofilaments assembled from subunits that do not share β2 m's native tertiary fold, but are formed from similar β-strands. The fibrils share motifs with other amyloid fibrils, but also contain unique features including π-stacking interactions perpendicular to the fibril axis and an intramolecular disulfide that stabilises the subunit fold. We also describe a structural model for a second fibril morphology and show that it is built from the same subunit fold. The results provide insights into the mechanisms of fibril formation and the commonalities and differences within the amyloid fold in different protein sequences. Impaired kidney function can lead to an increase of β2 -microglobulin (β2 m) serum levels, which can cause β2 m aggregation and amyloid fibril formation. Here the authors combine cryo-EM and magic angle spinning NMR measurements to determine the structure of a β2 m fibril and they also present the low resolution model of a β2 m fibril with a different morphology.